Scoping child mental health service capacity in South Africa disadvantaged communities: community provider perspectives. Issue 4 (28th November 2022) - Nhedzi, Abyshey; Haffejee, Sadiyya; O'Reilly, Michelle; Vostanis, Panos
Abstract : Purpose: This study aims to establish the perspectives of community providers on challenges and enablers in developing child mental health capacity in disadvantaged communities in South Africa. Design/methodology/approach: The authors involved 29 community providers operating in a large urban-deprived area in the Gauteng Province, east of Johannesburg. Community providers had educational, social and health care backgrounds. Their perspectives were captured through three focus groups, two participatory workshops and reflective diaries. Data were integrated and subjected to inductive thematic analysis. Findings: Three interlinked themes were identified. Community mobilization was viewed as pre-requisite through mental health awareness and strategies to engage children, youth and parents. Service provision should take into consideration contextual factors, predominantly inequalities, lack of basic needs and gender-based issues (domestic violence, teenage pregnancy and single motherhood). Participants referred to severe mental health needs, and related to physical health conditions, disabilities and impairments, rather than to common mental health problems or wellbeing. They proposed that capacity building should tap into existing resources and integrate with support systems through collaborative working. Practical implications: Child mental health policy and service design in Majority World Countries (MWCs), should involve all informal and structural support systems and stakeholders. Contextual factors require consideration, especially in disadvantaged communities and low-resource settings, and should be addressed through joined up working. Originality/value: Children's mental health needs are largely unmet in MWC-disadvantaged communities. These findings capture the experiences and perspectives of various community providers on how to enhance mental health provision by mobilizing communities and resources.